Pembelajaran Musik Tradisional Di SMA Negeri 1 Painan - Meggi Firnando; Harisnal Hadi (SENDRATASIK UNP, 2021)
This study aims to describe the learning planning applied at SMA 1 Painan. Students' high enthusiasm for music arts lessons and the many achievements in the field of music is proof that teachers have successfully implemented learning strategies. The method used in this research is descriptive qualitative research method. The subjects of this study were music art teachers, principals and some students of SMA 1 Painan. The object of this research is the learning strategy implemented at SMA 1 Painan. Data collection techniques used in this research are observation, interview and documentation. To test the validity of data in this study used source triangulation techniques, namely comparing between data sources with each other as material for data analysis. Data analysis techniques used in this research use interactive analysis techniques. There are four components, namely: 1) data collection techniques 2) data reduction 3) data presentation and 4) conclusion drawing. Based on the results of the research obtained conclusions that some musical arts learning strategies applied in SMA 1 Painan namely, 1) learning preparation; 2) learning management; 3) use of learning media; 4) application of learning methods, models and approaches; 5) approach to motivate students; 6) evaluation of learning.